2015
DOI: 10.5455/medscience.2014.03.8184
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis Paniculata (Burm. F.) Nees Induces Clinical and Sputum Conversion in Pulmonary Tuberculosis Patients

Abstract: The aim of this study was to determine whether Andrographus paniculata capsule induces clinical and sputum conversion in pulmonary tuberculosis (TB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because there are a limited number of studies evaluating the effects of botanical medicine on B. burgdorferi, it is helpful to draw on clinical studies that have shown benefit using botanical medicines for other spirochetal infections and infections like mycobacterium that are known to form antibiotic tolerant persister cells (35). For example, Andrographis has been shown to effectively treat leptospirosis in Chinese clinical trials (36) and improve clinical outcomes when combined with standard treatment for tuberculosis (37).…”
Section: Introductionmentioning
confidence: 99%
“…Because there are a limited number of studies evaluating the effects of botanical medicine on B. burgdorferi, it is helpful to draw on clinical studies that have shown benefit using botanical medicines for other spirochetal infections and infections like mycobacterium that are known to form antibiotic tolerant persister cells (35). For example, Andrographis has been shown to effectively treat leptospirosis in Chinese clinical trials (36) and improve clinical outcomes when combined with standard treatment for tuberculosis (37).…”
Section: Introductionmentioning
confidence: 99%
“…Because there are a limited number of studies evaluating the effects of botanical medicine on B. burgdorferi , it is helpful to draw on clinical studies that have shown benefit using botanical medicines for other spirochetal infections and infections like mycobacterium that are known to form antibiotic tolerant persister cells (39). For example, Andrographis has been shown to effectively treat leptospirosis in Chinese clinical trials (40, 41) and improve clinical outcomes when combined with standard antituberculosis treatment for TB (42).…”
Section: Introductionmentioning
confidence: 99%